Genome-wide Regulatory Roles of the C2H2-type Zinc Finger Protein ZNF764 on the Glucocorticoid Receptor - Fadda, Abeer (Sci Rep, 2017)
The C2H2-type zinc finger protein ZNF764 acts as an enhancer for several steroid hormone receptors, and haploinsufficiency of this gene may be responsible for tissue resistance to multiple steroid hormones including glucocorticoids observed in a patient with 16p11.2 microdeletion. We examined genome-wide regulatory actions of ZNF764 on the glucocorticoid receptor (GR) in HeLa cells as a model system. ZNF764- and GR-binding sites demonstrated similar distribution in various genomic features. They positioned predominantly around 50–500 kbs from the transcription start sites of their nearby genes, and were closely localized with each other, overlapping in ~37% of them. ZNF764 demonstrated differential on/off effects on GR-binding and subsequent mRNA expression: some genes were highly dependent on the presence/absence of ZNF764, but others were not. Pathway analysis revealed that these 3 gene groups were involved in distinct cellular activities. ZNF764 physically interacted with GR at ligand-binding domain through its KRAB domain, and both its physical interaction to GR and zinc finger domain appear to be required for ZNF764 to regulate GR transcriptional activity. Thus, ZNF764 is a cofactor directing GR transcriptional activity toward specific biologic pathways by changing GR binding and transcriptional activity on the glucocorticoid-responsive genes.